Tauhid As The Foundation of Inner Peace: A Study from The Perspective of The Qur’an and Islamic Psychology - Rodiyatam Mardiah; Safira Rahima Bajubair; Agung Pranoto Kadiatmaja (Journal Of Psychology, Counseling And Education, 2026)
This study explores Tawheed (the Oneness of God) as a psychological foundation for attaining Al-Nafs al-Mutmainnah (the tranquil soul) within the framework of Islamic psychology. It examines how Tawheed and Dhikr function as theological as theological and cognitive mechanisms that foster inner peace and emotional stability. Employing a library-based qualitative approach, this research analyzes classical Islamic texts and contemporary psychological studies to identify conceptual and empirical intersections. The analysis reveals that Tawheed, when internalized through spiritual cognition and ethical alignment, restructures human perceptions of anxiety, attachment, and self-control, producing a coherent sense of meaning and security. Furthermore, Dhikr practices demonstrate neuropsychological effects, including increased prefrontal cortex activity related to emotional regulation and reduced amygdala activation associated with fear responses, threby supporting their therapeutic value. These findings indicate that integrating Tawheed-based cognition with Dhikr practices forms a validated model for spiritual resilience and emotional well-being. The study concludes that Islamic psychology provides a holistic paradigm of mental health that bridges theological belief, psychological functioning, and neuroscientific evidence.